RNA polymerase activity in purified virions of avian reticuloendotheliosis viruses. - Mizutani, S (1976)
An RNA polymerase activity that synthesizes a U-rich RNA hydrogen bonded to a large viral RNA molecule was found in the cores of virions of avian reticuloendotheliosis viruses (REV). The RNA polymerase activity was separable from the DNA polymerase activity of REV virions. The 5'-terminus of the newly synthesized RNA was A. In addition, a tRNA nucleotidyl transferase activity, which added -CpCpA ends to tRNA, appears to be present in the REV virions.